Trade Openness Effect on Provincial Economic Growth in Indonesia - Saimul,; Arif Darmawan, (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This research aims to analyze the effect of openness on the economic growth of provinces in Indonesia. Using panel data from 2010 to 2017 in six provinces in Indonesia with investment and labor control variables, the results show that trade openness has an essential contribution to improving economic growth in Indonesia's provinces. The methodology of this study is use regression panel model. These results are following the concepts of theory and empiricism. However, because the degree of openness of provincial trade in Indonesia is still relatively low, the positive influence contributing to the domestic economy is also relatively low, from the control of foreign investment, FDI, and labor, which has a negative effect